Terror of the Radiance : Aššur Covenant to Yhwh Covenant - Thompson, Richard Jude (2013)
This study investigates Martin Noth’s conclusion about the Deuteronomistic History (DH) that the people of Israel had committed apostasy (Abfall), ceased to obey the law code of Yhwh, and thus lost their land. Scholars have challenged Noth’s hypothesis and even the existence of such a history. The present study adopts a thematic reading of the DH as a coherent corpus of writing with a consistent message. A close reading reveals a god, Yhwh, who declares war on other gods (’ĕlōhîm ’ăḥērîm) and commands his followers to conquer and to sanctify the mountain of the Emorites (har hā’ĕmōrî; Deut 1:7) and the land of Canaan (’ereṣ kənaʽan; Deut 32:49) to Yhwh. The sanctification includes the killing of the people living there: “When you attack them, you shall annihilate (haḥărēm taḥărîm) them entirely. Do not make a treaty with them and do not show mercy to them” (Deut 7:1–2). Throughout the DH, Yhwh and his spokespersons, the nəbî’îm, reward obedience and punish disobedience. Because the disobedient people of Israel fail to enforce Yhwh’s command to remove the nations of Canaan and their ’ĕlōhîm ’ăḥērîm, Yhwh enforces imperial law and sentences them to national death and exile. This study thus hypothesizes that the DH depicts an imperial, military covenant. After a survey of the inscriptions of the second-millennium b.c.e. Levant, the Hittite empire, the Neo-Assyrian empire, and the first-millennium b.c.e Levant, the study concludes with a hypothesis that the evidence points to the ideology of the Neo-Assyrian empire as the historical precedent for the Dtr covenant. The study challenges two presuppositions that underlie both the DH and its scholarship: that of the tôrāh as law and that of Yhwh as a unique god.